Tibial Plateau Slopes in Indian Patients with or without Anterior Cruciate Ligament Injury: A Magnetic Resonance Imaging Study. (December 2016) - Sundar, Shyam; Patnaik, Sarthak; Ubaydullaev, Bobur; Kolandavelu, Vinodh; Rajan, David
Purpose: To compare anterior cruciate ligament (ACL)–injured and ACL-intact patients as well as males and females in terms of tibial plateau slopes to determine their association with ACL injury. Methods: Magnetic resonance images (MRI) of the knee of 310 male and 179 female skeletally mature Indian patients (mean age, 40 years) with (n=170+29) or without (n=140+150) ACL injury were reviewed. Their medial and lateral tibial plateau slopes (MTPS and LTPS), medial tibial plateau depth (MTPD), and lateral tibial plateau height (LTPH) were measured using MRI. Results: The ACL-injured and ACL-intact groups were comparable in terms of MTPS (6.72° vs. 6.73°, p=0.07), LTPS (5.68° vs. 5.70°, p=0.09), MTD (1.74 vs. 1.73 mm, p=0.356), and LTH (2.21 vs. 2.22 mm, p=0.393). Males and females were also comparable in terms of MTPS and LTPS in both ACL-injured and ACL-intact groups. Conclusion: ACL-injured and ACL-intact patients as well as males and females were comparable in terms of the tibial plateau slope parameters.